A systemic framework and analysis of urban water energy. (November 2015) - Kenway, S.J.; Binks, A.; Lane, J.; Lant, P.A.; Lam, K.L.; Simms, A.
Abstract: Energy impacts of urban water systems are substantial, but not typically analysed systemically. We develop a new system boundary framework including a utility, the 'bulk water supply authority' (SB1); the 'urban water system' including water use (SB2); and the 'regional water system' (SB3). We use the framework to review existing models and show that most address only one boundary. We apply the framework to quantify thermal equivalents of water-related energy in SB1 and SB2, and identify that over 96% of water-related energy in South East Queensland (SEQ) is outside SB1 and within SB2. Consideration of energy influenced by water use is paramount to systemic energy efficiency and optimisation in the urban water system. Clear articulation of system boundaries will improve modelling and management of the energy impact of urban water. Systemic modelling will help decision makers answer increasingly integrated and cross-system and sector questions regarding water and energy interactions. Highlights: Defines boundaries for the water-energy system. Creates a framework for consistent analysis and management. Clarifies how models address parts of the energy effect of the water 'system'. Quantifies water-related energy across multiple boundaries.